Triple antiviral therapy in patient with liver cirrhosis: complications and options of pharmacological treatment - M. V. Mayevskaya; I. N. Tikhonov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss options of telaprevir application and risk of adverse events at triple antiviral therapy (AVT) in patients with the 1-st genotype of chronic hepatitis C and compensated liver cirrhosis (LC), and options of pharmacological treatment of hematological complications by original clinical case example.Key points. Introduction of NS3/4A protease inhibitor — telaprevir — to treatment mode for patients infected by the 1-st genotype of chronic hepatitis C, has allowed to increase treatment response rate considerably. Patients with LC who represent heterogenic group require the special approach. AVT with good efficacy and sufficient safety profile in patients with compensated cirrhosis, is as well as for patients in the Waiting list for liver transplantation currently possible. The most common complication of triple AVT are hematological adverse events — development of anemia, neutropenia and thrombocytopenia (or aggravation of severity of the latter in patients with severe fibrosis and LC). Nowadays thrombopoietin receptors agonist (eltrombopag) which allows to provide interferon-based AVT to patients with thrombocytopenia and to optimize it, is developed and approved for clinical application. Assessment of indications to thrombocytopoiesis stimulation, correction of dozes of drug and regular monitoring of peripheral blood parameters are important points.Conclusion. Introduction of direct antiviral agents — viral proteases inhibitors (telaprevir) to practice has allowed to increase AVT efficacy in patients with CHC G1 and liver cirrhosis providing comprehensible safety profile of AVT. Pharmacological stimulation of thrombocytopoiesis by thrombopoietin receptors agonists (eltrombopag) prior or during AVT has allowed not only to take into account patients with initially severe thrombocytopenia as candidates for AVT, but also to carry out sufficient treatment without decrease or with lower frequency of interferon doze reduction, achieving higher rate of sustained virologic response.